Characterization of the Trypanosoma cruzi Cdc2p-related protein kinase 1 and identification of three novel associating cyclins - Gomez, Eliana B. (2001)
Several Cdc2p-related protein kinases (CRKs) have been described in trypanosomatids but their role in the control of the cell cycle nor their biological functions have been addressed. In Trypanosoma cruzi two CRKs have been identified, TzCRK1 and TzCRK3. In this work we further characterize T. cruzi CRK1 and report the identification of three novel associating cyclins. We demonstrate that CRK1 levels and localization do not vary during the cell cycle, and show that it is localized in the cytoplasm, discrete regions of the nucleus, and is highly concentrated in the mitochondrion DNA (kinetoplast), suggesting a putative control function in this organelle. Using purified anti-CRK1 IgGs, we immunoprecipitated from the soluble fraction of T. cruzi epimastigote forms a protein kinase activity which is not inhibited by CDK inhibitors. In addition, we co-precipitated with p13Suc1p beads a kinase activity that was inhibited by the CDK inhibitor flavopiridol and olomoucine. Lastly, using the yeast two-hybrid system we identified three novel cyclin-like proteins able to associate with TzCRK1, and demonstrate that two of these cyclins also bind the T. cruzi CRK3 protein, indicating that these two CRKs are cyclin-dependent kinases.